Enterprise Risk Management Practices and Their Impact on Firm Performance: Evidence from Multinational Corporations - Nayme, Farah; Taybi, Imaane (University of Science and Computer Technology, 2025)
Global business environments have become increasingly volatile, pushing multinational corporations (MNC) to seek more resilient strategies for sustaining long-term performance. Enterprise Risk Management (ERM) has emerged as a critical framework, yet its effectiveness often depends on the interplay of governance diversity, digital transformation, and cultural adaptability. This study aims to examine how ERM, supported by these contextual factors, influences the performance of MNC operating in dynamic institutional settings. The research employs a quantitative approach, using survey data collected from 110 senior managers across multinational firms. Data were analyzed through Structural Equation Modeling (SEM) to test direct and mediated relationships between ERM practices and firm performance. The model integrates governance diversity, digital transformation, and cultural adaptability as complementary enablers that shape the effectiveness of ERM implementation. The results reveal that ERM positively contributes to firm performance when organizations embrace diverse governance structures, leverage digital tools, and nurture adaptive organizational cultures. Governance diversity strengthens decision-making and oversight, digital transformation enhances risk anticipation, and cultural adaptability ensures contextual alignment across markets. Together, these factors create a synergistic environment that amplifies ERM role in driving performance. The findings extend theoretical discussions on ERM by situating it within broader organizational and institutional contexts. Practically, they underscore the importance for managers to integrate ERM into corporate strategy while fostering diversity and digital readiness. For policymakers, the study suggests harmonizing disclosure standards and strengthening institutional frameworks to enhance corporate resilience.